A produção de conhecimento sob as influências sociais dos rankings acadêmicos: o caso QS world university rankings - Vicente, William Augusto (Universidade Federal de São Carlos, 2026)
This research, developed for the completion of a master's degree, sought to investigate the influences of world higher-education ranking-institutions on Brazilian scholarly production, based on their historical process of institutionalization. The investigation started from social circumstances surrounding these instruments, in which there is a lack of emphasis on the political, economic and institutional structures that sustain them. Through celebrations and various forms of consumption evident in the most widely used communication channels, these metrics increasingly circulate in specialized media, on university institutional portals and on academic social networks, thereby expanding their presence in the public debate. In this sense, we sought to analyze the structure of the historical processes that formed the foundational institutions for this type of classification, with emphasis on the properties of the ranking institution QS World University Rankings. Based on a framework concerning the political-social formation of public and private institutions and how these acquired predominance through the ideologies that underpin the State, we sought to analyze how the criteria used to evaluate these ranking institutions are interrelated with a historical-materialist understanding of institutions in the State, according to the narrower interests of specific groups that exert globalized influence. We emphasize that each element has political, social and, above all, economic foundations, which shape how publications occur and periodically influence the publications under evaluation. At the same time, the institutional agents affected by this ranking institution seek means to adapt their work according to the methodological determinations. As a result, an ambivalent relationship is observed in which science is valued more restrictively while at the same time providing ever more data to reinforce the criteria. Consequently, there is an uncritical consumption of these institutions due to insufficiently informed understanding of the criteria and purposes that sustain their existence.

Esta investigación, desarrollada para la finalización del máster, buscó investigar las influencias de las instituciones-ranking mundiales de la educación superior en la producción científica brasileña, a partir de su proceso de institucionalización histórica. La investigación partió de circunstancias sociales que rodean estas herramientas, en las que se constata la ausencia de atención a las estructuras políticas, económicas e institucionales que las sostienen. Mediante celebraciones y diversas formas de consumo verificadas en los canales de comunicación de mayor consumo, se pone de manifiesto que estas métricas circulan ampliamente en los medios especializados, en los portales institucionales de las universidades y en las redes sociales académicas, ampliando su presencia en el debate público. En este sentido, procuramos analizar la estructura de los procesos históricos que formaron las instituciones fundamentales para este tipo de clasificación, con énfasis en las propiedades de la institución-ranking QS World University Rankings. A partir de una estructuración sobre la formación político-social de las instituciones públicas y privadas y cómo estas fueron adquiriendo preponderancia a partir de las ideologías que participan en el sostenimiento del Estado, buscamos analizar cómo los criterios utilizados para evaluar estas instituciones-ranking se interrelacionan con una comprensión histórico-materialista de las instituciones en el Estado, conforme a intereses más restringidos de grupos específicos que ejercen una influencia globalizada. Destacamos que cada elemento posee fundamentos políticos, sociales y, sobre todo, económicos, que conducen la forma en que se realizan las publicaciones e influyen periódicamente en las publicaciones evaluadas. Al mismo tiempo, los agentes institucionales afectados por esta institución-ranking buscan medios para adecuar su trabajo, conforme a las determinaciones metodológicas. Como resultado, se observa una relación ambivalente en la que la ciencia es valorada de manera más restrictiva, al mismo tiempo que ofrece cada vez más datos para reforzar los criterios. En consecuencia, existe un consumo acrítico de estas instituciones, debido al insuficiente conocimiento informado sobre los criterios y las finalidades que sustentan su existencia.
Knowledge production under the social influences of academic rankings: the case of the qs world university rankings
La producción de conocimiento bajo las influencias sociales de los rankings académicos: el caso qs world university rankings
Keywords: Rankings; Economia; Ciência; Política; Alienação; Economy; Science; Politics; Alienation; Ciencia; Alienación; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade